Modified Simpson’s method for numerical integration problem / Nur Khairunnisa Md Khairi - Md Khairi, Nur Khairunnisa (2024)
Numerical method can be used to solve complicated integration problem that often occurs in mathematics, data analysis, physics and other fields research. This numerical method is often used when theoretical methods are cumbersome and difficult to implement. Some numerical method for solving integration problems includes Trapezoidal method, Simpson’s 1/3 method, Trapezium-corrected Simpson’s Method (TCSM) and Cubic-corrected Simpson’s Method (CCSM). This study aims to investigate the behaviour of these numerical methods in solving different integration problem. The performance of each numerical methods is analyze based on percentage of relative error. It is showed that Simpson’s 1/3 is the best method for solving integration problems.